Uptake of selected organic ligands by hardened cement paste: Studies on proxy ligands for the degradation of polyacrylonitrile and general considerations on the role of different functionalities in the uptake process - Szabo, P. G.; Tasi, A. G.; Gaona, X.; Maier, A. C.; Hedström, S.; Altmaier, M.; Geckeis, H. (Frontiers in Nuclear Engineering, 2022)
The uptake of α-hydroxyisobutyric acid (HIBA), 3-hydroxybutyric acid (HBA) and glutaric acid (GTA) by hardened cement paste (HCP) in the degradation stage II was investigated at various ligand concentrations (10–7 M ≤ [L]tot ≤ 0.1 M) and solid-to-liquid ratios (0.2 gdm–3 ≤ S:L ≤ 50 gdm–3). These organic ligands were previously identified as representative of the main degradation products of UP2W, a polyacrylonitrile-based material used as filter aid in nuclear power plants, under repository conditions. Sorption experiments were conducted with inactive (HIBA, HBA, GTA) and active (14C-labelled GTA) organic ligands. Sorption experiments show a weak uptake of HIBA and HBA by HCP, with distribution coefficients determined as Rd(HIBA) = (4.7±1.4) 10–3 m3kg–1 and Rd(HBA) = (3.0±0.9) 10–3 m3kg–1. A slightly stronger uptake is observed for GTA, i.e. Rd(GTA) = (1.3±0.5) 10–2 m3kg–1, likely reflecting the contribution from the ligand’s second carboxylate group. GTA follows a linear sorption behaviour within 10–7 M ≤ [GTA]tot ≤ 0.1 M, which was successfully modelled with a one-site Langmuir isotherm. The adsorption capacity determined for the uptake of GTA by HCP is slightly higher but in line with the capacity previously reported for isosaccharinic acid (ISA), whereas the affinity constant derived for GTA is significantly lower than values reported for stronger binding sites in HCP for the uptake of ISA. HIBA and HBA have a minor impact on the surface charge of HCP up to [L]tot ≈ 0.1 M. On the contrary, GTA induces a clear decrease in the surface charge above [GTA]tot ≈ 10–3 M resulting in an isoelectric point at [GTA]tot ≈ 6 10–2 M. Comparison of sorption data obtained in this work and reported in the literature for organic ligands containing the functional groups -COOH and -OH underlines the key role of multiple functionalities as a factor strengthening the interaction with the HCP surface. The participation of alcohol groups is particularly strong when present in their deprotonated state. These results provide information to quantitatively assess the uptake by HCP of organic ligands relevant in the context of nuclear waste disposal, and to understand their impact on the surface properties of cement.